Insect Venom Peptides - Palma, Mario Sergio [UNESP]; Kastin, A. J. (Elsevier B.V., 2006)
The insects of the order Hymenoptera ( bees, wasps, and ants) are classified in two groups, based on their life history: social and solitary. The venoms of the social Hymenoptera evolved to be used as defensive tools to protect the colonies of these insects from the attacks of predators. Generally they do not cause lethal effects but cause mainly inflammatory and/or immunological reactions in the victims of their stings. However, sometimes it is also possible to observe the occurrence of systemic effects like respiratory and/or kidney failure. Meanwhile, the venoms of solitary Hymenoptera evolved mainly to cause paralysis of the preys in order to permit egg laying on/within the prey's body; thus, some components of these venoms cause permanent/transient paralysis in the preys, while other components seem to act preventing infections of the food and future progenies. The peptide components of venoms from Hymenoptera are spread over the molar mass range of 1400 to 7000 da and together comprise up to 70% of the weight of freeze-dried venoms. Most of these toxins are linear polycationic amphipatic peptides with a high content of alpha-helices in their secondary structures. These peptides generally account for cell lysis, hemolysis, antibiosis, and sometimes promote the delivery of cellular activators/mediators through interaction with the G-protein receptor, and perhaps some of them are even immunogenic components. In addition to these peptides, the Hymenopteran venoms also may contain a few neurotoxins that target Na+ and/or Ca+2 channels or even the nicotinic ACh receptor. This review summarizes current knowledge of the biologically active Hymenoptera venoms.